Hypoalbuminemia is associated with adverse outcomes in critically ill children with cancer - James, Vinson; Ashcraft, Emily; Cheng, Cheng; Elbahlawan, Lama (Frontiers in Oncology, 2025)
IntroductionAcute kidney injury (AKI) is a serious complication encountered often in critically ill children with cancer. Hypoalbuminemia, commonly present in this population, has been associated with poor outcomes, including a higher rate of AKI. Studies examining the impact of hypoalbuminemia on outcomes in critically ill children with cancer are lacking. Therefore, the objective of this study was to investigate the impact of low serum albumin levels (SAL) on outcomes, including mortality and AKI, in critically ill children with oncologic/hematologic diseases. We also sought to examine the risk factors of AKI in this population.MethodsRetrospective review of all children with hematologic/oncologic disease admitted to the intensive care unit (ICU) from December 2020 to April 2021.ResultsA total of 82 patients were included in this study cohort. The median age in our cohort was 10.3 y (0.8, 22.3), and the most common diagnosis was hematologic malignancy (41%). Thirty percent of the cohort experienced AKI; 30% of these cases were severe. Risk factors for AKI included sepsis, antiviral medications, higher nephrotoxicity index, and a higher number of nephrotoxic drugs. The rate of AKI was higher in children with SAL <2.5 g/dL (55% vs 27% in children with SAL ≥2.5 g/dL, P=0.09). SAL <3 g/dL was associated with higher rate of invasive mechanical ventilation (IMV) (15% vs 2% in children with SAL≥3 g/dL, P=0.038) and a longer duration of ICU stay (4 days vs 2, P=0.028).ConclusionHypoalbuminemia is associated with adverse outcomes in children with oncologic/hematologic disease. Particularly, SAL < 3 g/dL are associated with higher need for IMV and longer ICU duration. Future studies are required to investigate the impact of hypoalbuminemia in this population and whether correcting hypoalbuminemia improves outcomes.